2004
DOI: 10.2320/matertrans.45.978
|View full text |Cite
|
Sign up to set email alerts
|

β-Tricalcium Phosphate Combined with Recombinant Human Bone Morphogenetic Protein-2: A Substitute for Autograft, Used for Packing Interbody Fusion Cages in the Canine Lumbar Spine

Abstract: The use of -tricalcium phosphate (-TCP) as osteoconductive and bone morphogenetic protein-2 (BMP-2) as osteoinductive bone graft substitutes has recently gained considerable research interest in spine surgery. However, whether the combination can be extrapolated to a successful interbody spinal arthrodesis remains uncertain. In this study, -TCP combined with recombinant human BMP-2 was examined in the canine lumbar spine model as a substitute for autograft used for packing interbody fusion cages. The discectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In other words, BMP can accelerate the degradation of β‐TCP scaffold, which provide sufficient space for new bone formation and remodeling. Ohyama et al . reported that the β‐TCP + BMP composite produced better interbody fusion rate and mechanical strength, and more bone trabecula in posterior lumbar fusion of dogs, compared with β‐TCP alone, autograft, and untreated groups.…”
Section: β‐Tcp + Recombinant Human Bmp‐2 (Rhbmp‐2)mentioning
confidence: 99%
“…In other words, BMP can accelerate the degradation of β‐TCP scaffold, which provide sufficient space for new bone formation and remodeling. Ohyama et al . reported that the β‐TCP + BMP composite produced better interbody fusion rate and mechanical strength, and more bone trabecula in posterior lumbar fusion of dogs, compared with β‐TCP alone, autograft, and untreated groups.…”
Section: β‐Tcp + Recombinant Human Bmp‐2 (Rhbmp‐2)mentioning
confidence: 99%
“…Before use, the stock solution was diluted in PBS. We choose a concentration of 200 mg rhBMP-2 on the basis of our in vitro assays with human osteoblast-like cells, our results from experiments in rats [26] and the known literature [30].…”
Section: Rhbmp-2mentioning
confidence: 99%
“…Despite the seminal work of Marshall Urist reported nearly four decades ago, showing a 12 times much greater de novo ectopic bone formation using the BMP-loaded b-TCP as compared to the BMP alone [3], there is still no routine use of BMPloaded b-TCP in the clinics. One of the most critical issues surrounding its potential clinical use is to understand the optimum three-dimensional structure of b-TCP and loading dose of BMP required for optimum bone regeneration and healing [24][25][26]. The effect of the three-dimensional structure of HA scaffolds on BMPinduced osteogenesis has been intensively investigated [27][28][29], but few studies have been conducted with b-TCP scaffolds.…”
Section: Introductionmentioning
confidence: 99%